Managing the Anti-corruption Security Process in the Organization - Jacek BIL (Communications of International Proceedings, 2021)
The purpose of this study is to identify limitations that hinder the process of introducing and maintaining an anti-corruption system in Polish enterprises. When the company's management board decides to adopt anti-corruption regulations, it is necessary to understand the benefits of transparent and malfunction-free operation. On the other hand, it is necessary to show the threats resulting from corrupt practices. The rules of the free market game adopted by economic entities that prosper in the reality of a consolidated democracy are based, inter alia, on the principles of social responsibility of each of the company's employees who, in certain cases, react to persistent irregularities by informing their superiors. In societies previously affected by the realities of a centrally planned economy, this kind of attitude is seen as denouncement, and no help is offered to those reporting non-compliance. Therefore, at the present stage, the organization of undertakings related to the collection of information from a whistleblower and its distribution in Polish practice is practically absent. Many representatives of business entities do not make any efforts to create mechanisms to limit or eliminate corruption, considering it a necessary aspect of running a business. The elimination of corrupt behavior is a necessary aspect of ensuring the company's security, because its consequences are based both on the individual responsibility of employees and the liability of collective entities. The pages of this article present the views of Polish entrepreneurs and company employees, illustrated by the author, in the context of introducing and maintaining an anticorruption system.
Keywords: Business; Corruption; Whistleblower; Security; Anti-Corruption System.